Devising chemically robust and cationic Ni(II)-MOF with nitrogen-rich micropores for moisture-tolerant CO2 capture: highly regenerative and ultrafast colorimetric sensor for TNP and multiple Oxo-anions in water with theoretical revelation - Goswami, Ranadip; Seal, Nilanjan; Dash, Soumya Ranjan; Tyagi, Anshu; Neogi, Subhadip (ACS Applied Materials & Interfaces, 2019)
Metal-organic frameworks (MOFs) show distinctive superiority for carbon dioxide (CO2) capture and luminescent sensing of toxic pollutants over other materials where combination of both of these properties together with improvement of hydrolytic stability and pore functionality is critical to environmental remediation applications. The Ni(II) framework [Ni-2(mu 2OH)(azdc)(tpim)](NO3)center dot 6DMA center dot 6MeOH (CSMCRI-3) (tpim = 44'4(2)-(1H-imidazole-245-triyl)tripyridine H(2)azdc = azobenzene-44'-dicarboxylic acid DMA = dimethylacetamide CSMCRI = Central Salt & Marine Chemicals Research Institute) encompassing cationic [Ni-2(mu(2)-OH)(CO2)(2)] SBUs is solvothermally synthesized from nitrogen-rich and highly fluorescent organic struts. The noninterpenetrated structure containing free nitrogen atom affixed microporous channels is stable in diverse organic solvents and weakly basic and acidic aqueous solutions. The activated MOF (3a) exhibits strong CO2-framework interaction and extremely selective CO2 adsorption over N-2 (292.5) and CH4 (11.7). Importantly water vapor exposure does not affect the surface area and/or multiple CO2 uptake-release cycles signifying potential of the porous structure for long-term use under humid conditions. Aqueous-phase sensing studies illustrate extremely specific and ultrafast detection of explosive 246-trinitrophenol (TNP) via remarkable fluorescence quenching (K-SV = 1.3 x 10 (5) M-1) with a 0.25 ppm limit of detection (LOD). Furthermore 3a serves as unique luminescent probe for highly discriminative and quick responsive detection of three noxious oxo-anions (Cr2O7 (2-) CrO4 (2-) MnO4-) in water via noteworthy turn-off responses and extreme low LODs (Cr2O7 (2-) 0.9; CrO4 (2-) 0.29; MnO4- 0.25 ppm). It is imperative to stress the outstanding reusability of the MOF toward multicyclic sensing of all four major water contaminants alongside visible colorimetric changes upon individual analyte detection. Mechanistic insights in light of the electron transfer route together with density functional theory calculations portray the influence of pore functionalization in framework-analyte interactions including alternation in energy levels where varying degrees of contribution of energy transfer explicitly authenticates high quenching of the material.
Keywords: chemically robust cationic MOF; DFT calculation; fast responsive detection; humid CO2 capture; TNP and oxo-anion sensing

Five concomitant polymorphs of a green fluorescent protein chromophore (GFPc) analogue: understanding variations in photoluminescence with pi-stacking interactions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Nikam, Shrikant B.; Puthuvakkal, Anisha; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2020)
The synthetically modified green fluorescent protein chromophore analogue 3,4,5-trimethoxybenzylidene imidazolinone (1) yielded five polymorphs (I, II, III, IV, V) concomitantly irrespective of the solvent used for crystallization. The pentamorphic modification of 1 is solely due to the interplay of iso-energetic weak intermolecular interactions in molecular associations as well as the conformational flexibility offered by a C-C single bond, which connects the electron-deficient moiety imidazolinone with the electron-rich trimethoxybenzylidene group. A common structural feature observed in all the polymorphs is the formation of a `zero-dimensional' centrosymmetric dimeric unit through a short and linear C-H center dot center dot center dot O hydrogen bond engaging phenyl C-H and imidazolinone carbonyl oxygen. However, the networking of these dimeric units showed a subtle difference in all the polymorphs. The 2D isostructurality was observed between polymorphs I, II and III, while the other two polymorphs IV and V revealed only `zero-dimensional' isostructurality. The different fluorescence emissions of Form I (blue) and Forms II to V (yellow) were attributed to the differences in pi-stacking interactions. It shows that one can modulate the photophysical properties of these smart materials by slightly altering their crystal structure. Such an approach will aid in developing new multi-colour organic fluorescent materials of varying crystal structures for live-cell imaging and fluorescent sensing applications.
Keywords: green fluorescent protein; hydrogen bonds; isostructurality; photoluminescence; pi-stacking; Polymorphs

[1,3]-Claisen rearrangement via removable functional group mediated radical stabilization - Alam, Md Nirshad; Dash, Soumya Ranjan; Mukherjee, Anirban; Pandole, Satish; Marelli, Udaya Kiran; Vanka, Kumar; Maity, Pradip (Organic Letters, 2021)
A thermal O-to-C [1,3]-rearrangement of alpha-hydroxy acid derived enol ethers was achieved under mild conditions. The 2-aminothiophenol protection of carboxylic acids facilitates formation of the [1,3] precursor and its thermal rearrangement via stabilization of a radical intermediate. Experimental and theoretical evidence for dissociative radical pair formation, its captodative stability via aminothiophenol, and a unique solvent effect are presented. The aminothiophenol was deprotected from rearrangement products as well as after derivatization to useful synthons.

Dual-catalyst engineered porous organic framework for visible-light triggered, metal-free and aerobic sp(3) C-H activation in highly synergistic and recyclable fashion - Kumar, Gaurav; Dash, Soumya Ranjan; Neogi, Subhadip (Journal of Catalysis, 2021)
Photoredox and organo-catalysis denote powerful construction tools for new classes of carbon-carbon bonds, where incisive amalgamation of both the approaches over a single, recyclable platform can bring about synergic and eco-friendly reactions under mild conditions. Aiming at enamine-based photoredox catalysis for atom-economic and metal-free sp(3 )C-H activation, an amide-based two-dimensional (2D) porous organic framework (POF) is devised. The pendent -NH2 groups are judiciously anchored with two catalytic stations viz. Rose Bengal and L-proline, through stepwise variation of solid phase peptide synthesis. The dual-catalyst engineered POF represents a fully organic material that synergistically performs visible-light triggered oxidative Mannich reaction to produce biorelevant heterocycle beta-amino ketone in excellent yield at room temperature, using oxygen as clean and selective oxidant. Importantly, activity of this bi-functionalized catalyst compares favorably well to individual homogeneous counterparts. The covalently modified framework demonstrates economic viability via gram-scale synthesis besides admirable reusability, and proves to be effective for nineteen varieties of substrates. The photocatalytic path is detailed from efficient energy transfer from host polymer to substrate in light of experimental and theoretical studies, which provides proof-of-concept to the photo-organo combined mechanism. The material benefits heterogenising two homogeneous catalysts, besides excluding additional steps of conventional Mannich reactions, and offers a step-forward to smart and green cross-dehydrogenative coupling reactions. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Atom-economy; C-H activation; Dual-catalyst engineering; Metal-free reaction; Photo-organo catalysis; Porous organic framework

Glycerol-triazole conjugated rhodamine as colorimetric and fluorimetric sensor for Cu2+ - Verma, Abhishek; Gahlyan, Parveen; Bawa, Rashim; Dash, Soumya Ranjan; Prasad, Ashok K.; Kumar, Rakesh (ChemistrySelect, 2021)
{A glycerol-triazole tethered rhodamine based colorimetric and fluorimetric sensor 3 `,6 `-bis(diethylamino)-2-(((1-(1,3-dihydroxypropan-2-yl)-1H-1,2,3-triazol-4 -yl)methylene)aminospiro [isoindoline-1,9 `-xanthen]-3-one (L1) is designed and synthesized for the selective recognition of Cu2+ ion. The sensor L1 allows naked eye detection of Cu2+ ion with a fast response (<1 min). Among the various metal ions tested, the sensor L1 shows selective binding with Cu2+ through turn-on fluorescence mechanism. The sensor shows 1 : 2 binding stoichiometry with binding constant
Keywords: Cu2+ Sensor; DFT; Glycerol; Rhodamine B; Triazole

Insights into chemical reactions at the beginning of the universe: from HeH+ to H-3 (+) - Dash, Soumya Ranjan; Das, Tamal; Vanka, Kumar (Frontiers in Chemistry, 2021)
At the dawn of the Universe, the ions of the light elements produced in the Big Bang nucleosynthesis recombined with each other. In our present study, we have tried to mimic the conditions in the early Universe to show how the recombination process would have led to the formation of the first ever formed diatomic species of the Universe: HeH+, as well as the subsequent processes that would have led to the formation of the simplest triatomic species: H-3 (+). We have also studied some special cases: higher positive charge with fewer number of hydrogen atoms in a dense atmosphere, and the formation of unusual and interesting linear, dicationic He chains beginning from light elements He and H in a positively charged atmosphere. For all the simulations, the ab initio nanoreactor (AINR) dynamics method has been employed.
Keywords: ab initio molecular dynamics; ab initio nanoreactor; Density functional theory; origin of molecules in the universe; the earliest lewis acid

Phosphite mediated asymmetric N to C migration for the synthesis of chiral heterocycles from primary amines - Rani, Soniya; Dash, Soumya Ranjan; Bera, Asish; Alam, Md Nirshad; Vanka, Kumar; Maity, Pradip (Chemical Science, 2021)
A phosphite mediated stereoretentive C-H alkylation of N-alkylpyridinium salts derived from chiral primary amines was achieved. The reaction proceeds through the activation of the N-alkylpyridinium salt substrate with a nucleophilic phosphite catalyst, followed by a base mediated [1,2] aza-Wittig rearrangement and subsequent catalyst dissociation for an overall N to C-2 alkyl migration. The scope and degree of stereoretention were studied, and both experimental and theoretical investigations were performed to support an unprecedented aza-Wittig rearrangement-rearomatization sequence. A catalytic enantioselective version starting with racemic starting material and chiral phosphite catalyst was also established following our understanding of the stereoretentive process. This method provides efficient access to tertiary and quaternary stereogenic centers in pyridine systems, which are prevalent in drugs, bioactive natural products, chiral ligands, and catalysts.

Prominence of Cu in a plasmonic Cu-Ag alloy decorated SiO2@S-doped C3N4 core-shell nanostructured photocatalyst towards enhanced visible light activity - Babu, Pradeepta; Dash, Soumya Ranjan; Behera, Arjun; Vijayaraghavan, T.; Ashok, Anuradha; Parida, Kulamani (Nanoscale Advances, 2021)
A series of Cu-Ag bimetal alloys decorated on SiO2 and the fabrication of few-layer S-doped graphitic carbon nitride (SC) warped over it to form a core-shell nanostructured morphology have been demonstrated and well characterized through various physiochemical techniques. HRTEM data confirmed the formation of a compact nanojunction between the SiO2 and SC, where Cu-Ag is embedded uniformly with an average particle size of 1.3 nm. The Ag : Cu (1 : 3) between SiO2 and SC produces 1730 mu mol h(-1) g(-1) of H-2 under visible light illumination. Moreover, 6.2-fold current enhancement in the case of Ag : Cu (1 : 3) as compared to the Ag-loaded core-shell nanostructured photocatalyst indicates higher electron-hole-pair separation. The excellent activity was due to the synergistic alloying and plasmonic effect of Ag and Cu. DFT studies reveal that the Cu atom in the Cu-Ag bimetal alloy plays a pivotal role in the generation of H-2, and the reaction proceeds via a 4-membered transition state. The mechanistic insight proceeds from the generation of hot electrons due to the LSPR effect and their transfer to the SC layer via a compact nanojunction.

Direct (hetero)arylation (DHAP) polymerization of conjugated polymers - new A-B-A monomer design for P(NDI2OD-T2) & the challenges of adopting DHAP for continuous flow processes - Kakde, Navnath R.; Bharathkumar, H. J.; Wavhal, Bhaiyyasaheb A.; Nikam, Arun; Patil, Suneha; Dash, Soumya Ranjan; Vanka, Kumar; Krishnamoorthy, K.; Kulkarni, Amol; Asha, S. K. (Journal of Materials Chemistry C, 2022)
P(NDI2OD-T2), also known as Polyera ActivInk N2200, was synthesized by the atom-economic direct hetero arylation polymerization (DHAP) route using a newly designed A-B-A monomer. The new monomer design involved flanking naphthalene diimide with bithiophene units in the bay position, which was further polymerized with bay substituted 1,4-dibromo naphthalene diimide, to afford the same polymer structure as P(NDI2OD-T2). The new monomer design resulted in a very high molecular weight (M-n: 99.5 kDa, D-M: 2.8) defect-free polymer in a quantitative yield by the DHAP batch process using 1,2,4-trichlorobenzene (TCB) as the solvent. DFT studies revealed that the abstraction of the alpha-proton from the naphthalene diimide substituted 2,2 `-bithiophene was favorable by 2.6 kcal mol(-1) (Delta Delta G) as compared to that from 2,2 `-bithiophene. The reason for this improved C-H activation at the alpha position can be attributed to the presence of C-HMIDLINE HORIZONTAL ELLIPSIS pi stabilizing interactions in naphthalene diimide substituted 2,2 `-bithiophene, which strengthens upon the extended charge delocalization throughout the ring, thus stabilizing the conjugate base generated after the proton abstraction. Continuous flow polymerization was carried out by pumping the DHAP reaction mixture including the monomers, catalyst, and additive (pivalic acid) solubilized in degassed TCB through a pre-heated glass condenser packed with K2CO3 and Celite under aerobic conditions. Reproducible molecular weights of M-n: 29.5 kDa, D-M: 1.7 were obtained at much lower concentrations of reactant mixture compared to that for batch polymerization. This is the first report of the synthesis of P(NDI2OD-T2) by a Continuous Flow Process adopting the DHAP route to obtain a defect-free polymer with reasonable molecular weights. P(NDI2OD-T2) was also synthesized by Stille polymerization as a reference control sample to compare the thermal and charge carrier transport properties of the DHAP polymers. Organic field-effect (OFET) mobility measurements indicated mobility values in the order of 10(-3) cm(2) V-1 s(-1) for the DHAP batch polymer (using the novel monomer design). The P(NDI2OD-T2) synthesized by DHAP batch using the commonly used starting materials - bisbromo naphthalene diimide and bithiophene, exhibited OFET mobilities which were one order less, similar to 10(-4) cm(2) V-1 s(-1). This observation highlights the importance of structural design in the monomer to enhance reactivity and thereby the bulk properties using the DHAP route.

Enantioselective Cu(I)-catalyzed borylative cyclization of enone-tethered cyclohexadienones and mechanistic insights - Jadhav, Sandip B.; Dash, Soumya Ranjan; Maurya, Sundaram; Nanubolu, Jagadeesh Babu; Vanka, Kumar; Chegondi, Rambabu (Nature Communications, 2022)
Rapidly building molecular structures with both elements of complexity and flexibility is a key goal of organic synthesis. Here the authors show a tandem copper-catalyzed beta-borylation/Michael addition on prochiral enone-tethered 2,5-cyclohexadienones, to generate bicyclic borylated products in high yield and enantioselectivity. The catalytic asymmetric borylation of conjugated carbonyls followed by stereoselective intramolecular cascade cyclizations with in situ generated chiral enolates are extremely rare. Herein, we report the enantioselective Cu(I)-catalyzed beta-borylation/Michael addition on prochiral enone-tethered 2,5-cyclohexadienones. This asymmetric desymmetrization strategy has a broad range of substrate scope to generate densely functionalized bicyclic enones bearing four contiguous stereocenters with excellent yield, enantioselectivity, and diastereoselectivity. One-pot borylation/cyclization/oxidation via the sequential addition of sodium perborate reagent affords the corresponding alcohols without affecting yield and enantioselectivity. The synthetic potential of this reaction is explored through gram-scale reactions and further chemoselective transformations on products. DFT calculations explain the requirement of the base in an equimolar ratio in the reaction, as it leads to the formation of a lithium-enolate complex to undergo C-C bond formation via a chair-like transition state, with a barrier that is 22.5 kcal/mol more favourable than that of the copper-enolate complex.

Hybrid material for ferric ion detection & remediation: exceptional selectivity & adsorption capacity with biological applications - Yadav, Sanjay; Rajpurohit, Dushyantsingh; Dash, Soumya Ranjan; Bhojani, Gopal; Chatterjee, Shruti; Paital, Alok Ranjan (Microporous and Mesoporous Materials, 2022)
In this work, naphthalimide derived functionalized silica material SiO2@NAPIA (2,2'((((propylazanediyl)bis (methylene))bis(2,1-phenylene))bis(oxy))bis(N-(1,3-dioxo-1H-benzo[de]i soquinoline-2(3H)-yl)acetamide)) was constructed as a dual signaling and remediation material for ferric ions from a pool of 35 common ions (cations and anions) in the aqueous system. The material Cubic SiO2 shows a high surface area (1104 m2/g, pore volume (1.510 cm3/g), and pore diameter (6.3 nm) in the mesoporous range, which reduces further on functionalization to get the final material SiO2@NAPIA. The ferric ion selectivity through fluorescence quenching displays a SternVolmer quenching constant (Ksv) of 7.8 x 108 M-1 with a LOD (Limit of detection) value of 0.11 mu M for ferricion, which is 48 times lower than the USEPA (United States Environmental Protection Agency) maximum contaminant level (5.35 mu M) in drinking water. This material also shows a very high adsorption capacity (664 mg/g) for ferric ions fitting the Langmuir model isotherm with R2 = 0.99, which can be easily stripped out, and the material can be recycled. This material was also used as a sensory probe material for biosensing of ferric ions through fluorescence imaging in living organisms like Artemia salina and quantification in the real environmental sample. Furthermore, the antibacterial activity inspired by the ferric ion chelating affinity shows good potency against several Gram-negative and Gram-positive bacterial strains. The Minimum Inhibitory Concentration (MIC) & Minimal Bactericidal Concentration (MBC) of the material against these pathogens were found to be 100 & 200 mu g/mL respectively. This material signifies superior activity with respect to the ferric-ion selective materials known in the literature.
Keywords: Adsorption; Antibacterial; Biosensing; Functional material; Mesoporous silica; sensing

Luminescent magnesium complexes with intra- and inter-ligand charge transfer - Kumar, Rohit; Pahar, Sanjukta; Chatterjee, Joy; Dash, Soumya Ranjan; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2022)
Herein, we report two 2,2'-pyridylpyrrolide (PyPyrH) ligand supported magnesium complexes (1 and 2), which demonstrate bright luminescence with a quantum yield of 22% and 14% in the solid state, respectively. Theoretical calculations reveal that their emissive properties originate from the intra- and inter-ligand charge transfer.

Mechanistic insight the visible light driven hydrogen generation by plasmonic Au-Cu alloy mounted on TiO2 @B-doped g-C3N4 heterojunction photocatalyst - Babu, Pradeepta; Dash, Soumya Ranjan; Parida, Kulamani (Journal of Alloys and Compounds, 2022)
Designing of two dimensional surfaces and interfaces with light-active materials has been established as a versatile approach to increase their photocatalytic activity. In the present work, n-type anatase TiO2 coupled with p-type B-doped g-C3N4 nanosheet (BCN) were fabricated and Au-Cu nanoalloy with varying atomic ratio were deposited on the p-n heterojunction. The incorporation of Au-Cu on the interface of the dyad enhances light absorption over broad regime, charge separation, and migration. Au-Cu with 1:1 ratio (with an average particle size of 1.2 nm) loaded p-n hetrojunction (TBCAC-1:1) shows excellent photocurrent enhancement (approximately 4.4-folds) in the cathodic direction as compared to their monometallic plasmonic counterpart. Additionally, the catalyst shows photocurrent at zero biased potential as well as lower onset potential as compared to the other alloy. TBCAC-1:1 photocatalyst could able to produce 2150 mu mol h(-1)g(-1) of hydrogen, which is (approximately 3-folds) as compared to their monometallic counterparts. The hydrogen evolution process for Au-Cu (1:1) system was found to be governed by the charge distribution which dictates the binding preference of the Au and Cu sites leading to the water splitting as investigated by DFT calculation. The excellent hydrogen generation by the photocatalyst links to the synergistic effect between Au and Cu associated with the hot electron photochemistry due to surface plasmon resonance phenomenon. (C) 2022 Published by Elsevier B.V.
Keywords: Doped carbon nitride; hydrogen production; LSPR; P-n junction; Photocatalysis; Plasmonic alloy

Polymorphs of green fluorescence protein chromophore analogue: fluorescence switching with thermal stimuli - Mali, Bhupendra P.; Dash, Soumya Ranjan; Biswas, Anupam; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Crystal Growth & Design, 2022)
Polymorphs of fluorescent organic materials offer significant implications in optoelectronics and advanced materials as they modulate photoluminescence properties. A slight alteration in the conformation/packing of molecules in the crystals shows variation in photoluminescence. This necessitates the polymorph screening of these materials to develop novel crystalline forms with distinct fluorescence emissions for broader application. In continuation of our work on the polymorph screening of Green Fluorescence Protein Chromophore (GFPc), we have synthesized a new imidazoline derivative, ethyl (Z)-2-(2-methyl-5-oxo-4-(3,4,5-trimethoxybenzylidene)-4,5-dihydro-1H-imi dazol-1- yl)acetate (1). Polymorph screening of 1 under different crystallization conditions revealed three polymorphs, Form I (needle), Form II (block), and Form III (polycrystalline material). Forms I and II are the outcome of solution crystallization, whereas Form III was produced from the melt crystallization of Forms I and II. DSC, HSM, and powder and single-crystal XRD studies indicate the conversion of Form I and Form III crystals to Form II crystals on thermal stimuli. The photoluminescence studies revealed cyan, yellow, and yellowish-green fluorescence emission for Forms I, II, and III crystals, respectively. The difference in photoluminescence could be due to the variance in aggregation modes like H-aggregation in Form I and J-aggregation in Form II crystals. Form I, Form II, and Form III crystals also showed irreversible thermal fluorescent switching from cyan-yellow-green due to polymorphic phase transitions. The study correlates the direct observation of the modulation of the excited-state transition under thermal stimuli in the crystalline phase. It will help augment the pace in the research of thermally responsive fluorescent materials.

Predicting the redox potentials of phenazine derivatives using DFT-assisted machine learning - Ghule, Siddharth; Dash, Soumya Ranjan; Bagchi, Sayan; Joshi, Kavita; Vanka, Kumar (ACS Omega, 2022)
This study investigates four machine-learning (ML) models to predict the redox potentials of phenazine derivatives in dimethoxyethane using density functional theory (DFT). A small data set of 151 phenazine derivatives having only one type of functional group per molecule (20 unique groups) was used for the training. Prediction accuracy was improved by a combined strategy of feature selection and hyperparameter optimization, using the external validation set. Models were evaluated on the external test set containing new functional groups and diverse molecular structures. High prediction accuracies of R2 > 0.74 were obtained on the external test set. Despite being trained on the molecules with a single type of functional group, models were able to predict the redox potentials of derivatives containing multiple and different types of functional groups with good accuracies (R2 > 0.7). This type of performance for predicting redox potential from such a small and simple data set of phenazine derivatives has never been reported before. Redox flow batteries (RFBs) are emerging as promising candidates for energy storage systems. However, new green and efficient materials are required for their widespread usage. We believe that the hybrid DFT-ML approach demonstrated in this report would help in accelerating the virtual screening of phenazine derivatives, thus saving computational and experimental costs. Using this approach, we have identified promising phenazine derivatives for green energy storage systems such as RFBs.

Activation of the olefinic C-H bond of NHC and NHO by perimidine-based silicon and germanium compounds - Gour, Kritika; Pramanik, Debjit; Dash, Soumya Ranjan; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2023)
In this manuscript, several backbonegermylene-functionalized zwitterioniccompounds were prepared conveniently from the corresponding N-heterocycliccarbenes or N-heterocyclic olefins in a single step through backboneC-H activation. Our initial motivation was to generate a silylenefrom C10H6(Me3SiN)(2)SiHCl(2) using ItBu [ItBu= (1,3-ditert-butyl)imidazol-2-ylidene], but instead, the reactionled to deprotonation from the imidazolium backbone of ItBu, forming the imidazolium salt with a silyl backbone at the C4position (3). We presumed that the reaction proceededthrough the generation of an ephemeral silylene. We subsequently preparedthe analogous germylene (4) and reacted it with IDipp[IDipp = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene], ItBu, and IDipp=CH2. Spectroscopic and crystallographicanalysis of these complexes revealed that, in all cases, there wasdeprotonation from the backbone and formation of zwitterionic products(5-7). When the hydrogen in the NHCbackbone was replaced with methyl groups such as IDipp(Me) (1,3-bis(2,6-diisopropylphenyl)-4,5-dimethylimidazol-2-ylidene),simple adduct formation occurred, exemplified by the isolation ofIDipp(Me)& BULL;Ge(NSiMe3)(2)C10H6 (8).

Cocrystal approach to modulate the photoluminescent properties of a GFP chromophore analogue: role of halogen/hydrogen bonding in achieving a wide range of solid-state fluorescence emissions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Annadhasan, Mari; Biswas, Anupam; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (Crystal Growth & Design, 2023)
Fine-tuning the photophysical properties of fluorescentorganicsolids is essential to attain multicolor displays and meet the demandfor futuristic light-emitting materials. Here, we report the tunableluminescence of a green fluorescent protein (GFP) chromophore analogue,3,4,5-TIA (A), based on the formation of two-component molecular cocrystalswith six different coformers. Coformers selected to synthesize thebinary cocrystals include 1,4-diiodotetrafluorobenzene (B), perfluoronaphthalene(C), 1,4-dibromotetrafluorobenzene (D), 2,3,5,6-tetrafluoroterephthalicacid (E), benzene-1,2,4,5-tetracarbonitrile (F), and benzene-1,2,4,5-tetracarboxylicacid (G). Interestingly, the cocrystals A center dot C and A center dot Fshowed molecular crystal polymorphism with a slight variation in fluorescence,revealing an aggregation-induced emission (AIE). A crystal structureanalysis showed the interplay of hydrogen bonding, halogen bonding,and aromatic pi-stacking interactions in associating neutralsolid components in the cocrystal. All of the novel cocrystals displayeda wide range of photoluminescence ranging from blue to dark orange.The time-dependent density functional theory (TD-DFT) calculationsindicate the changes in the energy level structures (HOMO to LUMO)in cocrystals that resulted in variations in fluorescence emission.The study aims to further understand the structure-propertyrelationship between molecular arrangement and photoluminescence. Cocrystals of a GFPc analogue with differentcoformers displayeda wide range of fluorescence emissions ranging from blue to dark orangewith varying quantum yields. With similar geometries of pi-stackinginteractions, hydrogen and halogen bonding have played a vital rolein fine-tuning the photoluminescence; halogen bonding leads to a blueshift, and hydrogen bonding results in a red shift.

Enhancing diradical character of chichibabin's hydrocarbon through fluoride substitution - Kundu, Gargi; Dash, Soumya Ranjan; Kumar, Ravi; Vanka, Kumar; Ghosh, Aryya; Sen, Sakya S. (ChemPlusChem, 2023)
In this work, 5-SIDipp [SIDipp=1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] (1) derived Chichibabin's hydrocarbon with an octafluorobiphenylene spacer (3) has been reported. The addition of two equivalents of 5-SIDipp with decafluorobiphenyl in presence of BF3 gives the double C-F bond activated imidazolium salt with two tetrafluoroborate anions, 2. Further reduction of 2 gives the fluorine substituted 5-SIDipp based Chichibabin's hydrocarbon, 3. Quantum chemical calculations suggested a singlet state of 3 with a singlet-triplet energy gap (?ES-T) of 3.7 kcal mol(-1), which is substantially lower with respect to the hydrogen substituted NHC-based Chichibabin's hydrocarbons (10.7 kcal mol(-1), B3LYP). As a result, the diradical character (y) of 3 (y=0.62) is also noticeably higher than the hydrogen substituted CHs (y=0.41-0.43). The ?ES-T was found to be higher in CASSCF (22.24 kcal mol(-1)) and CASPT2 (11.17 kcal mol(-1)) for 3 and the diradical character (d) is 44.6 %.
Keywords: C-F Bond Activation; Chichibabin & PRIME; DFT; N-Heterocyclic carbene; s Hydrocarbon

Six-membered NHC stabilized monomeric zinc complexes - Gour, Kritika; Kundu, Gargi; Dash, Soumya Ranjan; Vanka, Kumar; Tothadi, Srinu; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2023)
This paper describes the rare use of a 6-membered saturated N-heterocyclic carbene (NHC) known as 1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene (abbreviated as 6-SI-Dipp) as a ligand in zinc chemistry. We report on the investigation of the reactions between 6-SI-Dipp and ZnX2, which resulted in a range of new monomeric 6-SIDipp center dot ZnX2 complexes (X=Et (1), Cl (2), Br (3), and I (4)). We also prepared a new NHC zinc complex where the two substituents of the zinc atom are different, 6-SIDipp center dot Zn(Et)Br (7) through the reaction of the proligand [6-SIDippH]Br with ZnEt2. We have observed that the reactions of complex 1 with sulfur and HBpin led to the removal of the ZnEt2 moiety, resulting in the formation of a C=S double bond and a B H activation product, respectively. Lastly, the reaction of 1 with five-membered NHCs led to the exchange of carbene and the formation of either 5-IDipp center dot ZnEt2 (8) or 5-SIDipp center dot ZnEt2 (9).
Keywords: Lewis adduct; NHC; X-ray diffraction; zinc

Thermally activated delayed fluorescent solvent-free organic liquid hybrids for tunable emission applications - Nidhankar, Aakash D. D.; Goudappagouda; Kothavade, Premkumar D.; Dongre, Sangram D.; Veer, Sairam Dnyaneshwar; Dash, Soumya Ranjan; Rajeev, Kavya; Unni, K. N. Narayanan; Shanmuganathan, Kadhiravan; Babu, Sukumaran Santhosh (Chemistry-An Asian Journal, 2023)
The synthetic feasibility and excellent luminescence features of organic molecules attracted much attention and were eventually found useful in lighting applications. In this context, a solvent-free organic liquid having attractive thermally activated delayed fluorescence features in bulk along with high processability has prime importance. Herein, we report a series of naphthalene monoimide-based solvent-free organic liquids exhibiting cyan to red thermally activated delayed fluorescence with luminescence quantum yields up to 80% and lifetimes between 10 to 45 mu s. An effective approach explored energy transfer between liquid donors with various emitters exhibiting tunable emission colors, including white. The high processability of liquid emitters improved the compatibility with polylactic acid and was used for developing multicolor emissive objects using 3D printing. Our demonstration of the thermally activated delayed fluorescence liquid will be much appreciated as a processable alternate emissive material suitable for large-area lighting, display, and related applications.
Keywords: 3D printing; Energy Transfer; OLED; Organic Liquids; TADF

Exploring unconventional σ-hole interactions: computational insights into the interaction of XeO3 with non-aromatic coordinating solvents - Dash, Soumya Ranjan; Vanka, Kumar (Chemphyschem, 2024)
In order to control the explosiveness and shock sensitivity of XeO3, we have investigated its plausible interaction with various non-aromatic coordinating solvents, serving as potential Lewis base donors, through density functional theory (DFT) calculations. Out of twenty six such solvents, the top ten were thus identified and then thoroughly examined by employing various computational tools such as the mapping of the electrostatic potential surface (MESP), Wiberg bond indices (WBIs), non-covalent interaction (NCI) plots, Bader's theory of atoms-in-molecules (AIM), natural bond orbital (NBO) analysis, and the energy decomposition analysis (EDA). The amphoteric nature of XeO3 was also explored by investigating the extent of back donation from the lone pair of Xe to the antibonding orbital of the donating atom/group of the solvent molecules. The C-H & mldr;O interactions were also found to be a contributing factor in the stabilization of these adducts. Although these aerogen-bonding interactions were found to be predominantly electrostatic, significant contributions from the orbital contributions, as well as dispersion interactions, were observed. The top three non-aromatic solvents (among the twenty six studied) which form the strongest adducts with XeO3 are proposed to be hexamethylphosphoramide (HMPA), N,N `-dimethylpropyleneurea (DMPU) and tetramethylethylenediamine (TMEDA).
Keywords: Aerogen bonding; Non-Aromatic Solvents; non-covalent interactions; Sigma-hole; XeO3

Size matters: computational insights into the crowning of noble gas trioxides - Dash, Soumya Ranjan; Sharma, Himanshu; Tiwari, Mrityunjay K.; Greb, Lutz; Vanka, Kumar (Inorganic Chemistry, 2024)
In pursuit of enhancing the stability of the highly explosive and shock-sensitive compound XeO3, we performed quantum chemical calculations to investigate its possible complexation with electron-rich crown ethers, including 9-crown-3, 12-crown-4, 15-crown-5, 18-crown-6, and 21-crown-7, as well as their thio analogues. Furthermore, we expanded our study to other noble gas trioxides (NgO(3)), namely, KrO3 and ArO3. The basis set superposition error (BSSE) corrected interaction energies for these adducts range from -13.0 kcal/mol to -48.2 kcal/mol, which is notably high for sigma-hole-mediated noncovalent interactions. The formation of these adducts was observed to be more favorable with the increase in the ring size of the crowns and less favorable while going from XeO3 to ArO3. A comprehensive analysis by various computational tools such as the mapping of the electrostatic potential (ESP), Wiberg bond indices (WBIs), Bader's theory of atoms-in-molecules (AIM), natural bond orbital (NBO) analysis, noncovalent interaction (NCI) plots, and energy decomposition analysis (EDA) revealed that the C-H center dot center dot center dot O interactions, as well as dispersion interactions, play a pivotal role in stabilizing adducts involving larger crowns. A noteworthy outcome of our study is the revelation of a coordination number of 9 for xenon in the complex formed between XeO3 and the thio analogue of 18-crown-6, which is higher than the largest number reported to date.

Taming XeO3 with aza-crowns: computational studies into σ-hole mediated host-guest interactions - Dash, Soumya Ranjan; Vanka, Kumar (ChemPhysChem, 2024)
Various aza-crowns with different sizes and substituents have been explored computationally as potential hosts for stabilizing the explosive guest xenon trioxide (XeO3) through sigma-hole-mediated aerogen bonding interactions. Interestingly, aza-crowns demonstrate superior binding towards XeO3 compared to their oxygen and thio counterparts. However, unlike the latter cases, where the binding was found to be increasingly favorable with the increase in the size of the crowns, aza-crowns exhibit a variable size preference for XeO3, peaking with aza-15-crown-5, and reducing thereafter with increase in crown size.
Keywords: aza-crowns; host-guest systems; noncovalent interactions; sigma (sigma) hole; Xenon

Unprecedented C-F bond cleavage in perfluoronaphthalene during cobaltocene reduction - Kundu, Gargi; Pramanik, Debjit; Dash, Soumya Ranjan; Kumar, Ravi; Sangole, Mayur; Tothadi, Srinu; Ghosh, Aryya; Vanka, Kumar; Singh, Kirandeep; Sen, Sakya S. (DALTON TRANSACTIONS, 2024)

Unravelling the prebiotic origins of the simplest α-ketoacids in cometary ices: a computational investigation - Dash, Soumya Ranjan; Pandya, Rinu; Singh, Geetika; Sharma, Himanshu; Das, Tamal; Haldar, Hritwik; Hotha, Srinivas; Vanka, Kumar (CHEMICAL COMMUNICATIONS, 2024)
Keywords: GLYOXYLATE; Hydrocarbons; Metabolism; Precursors

Unveiling the inverse sandwich complexes of XeO3: a computational exploration - Dash, Soumya Ranjan; Vanka, Kumar (Inorganic Chemistry, 2024)
Our study introduces the design of inverse sandwich (iSw) complexes incorporating a noble gas compound: xenon trioxide (XeO3). Through comprehensive computational analyses, we have investigated the critical factors influencing their stability by employing a variety of state-of-the-art computational tools. We demonstrated that the coordination number of xenon in the iSw complex of XeO3 with 18-crown-6 is influenced by the presence of a rare, weakly stabilizing XeXe interaction between the XeO3 molecules. Furthermore, we observed that the stability of iSw complexes of 1,3,5-triphenylbenzene (TPB) and its derivatives is not solely attributed to aerogen bonding, but also involves contributions from C-HO interactions and back-donation from the lone pair of Xe to the antibonding C-C orbitals of TPB. Additionally, the significant contributions from orbital interactions and dispersion interactions in the TPB derivatives highlight the multifaceted amphoteric properties of XeO3 and reveal that the iSw complexes of TPB and derivatives are not predominantly governed by electrostatic interactions, contrary to conventional belief.

Ce[N(SiMe3)2]3(THF)3-catal yzed hydroboration of CO2, esters and epoxides with pinacolborane: selective synthesis of methanol in multigram scale - Hossain, Md Jabed; Shah, Brij Kumar; Dash, Soumya Ranjan; Vanka, Kumar; Khan, Shabana (Chemistry-A European Journal, 2025)
In this work, we have reduced CO2 with HBpin to afford borylated methanol product selectively in similar to 99 % yield using Ce[N(SiMe3)(2)](3)(THF)(3) as a catalyst. This led to multigram scale isolation of methanol obtained from CO2 reduction via the hydrolysis of borylated methanol, this establishes the potential of Ce[N(SiMe3)(2)](3)(THF)(3) as an efficient homogeneous catalyst for the bulk scale methanol synthesis. A practical application of this catalytic system was also shown by reducing CO2-containing motorbike exhaust efficiently and selectively. Further, C-O bond activation of esters and epoxides using HBpin and 1-2 mol % of Ce[N(SiMe3)(2)](3)(THF)(3) at 60 degrees C afforded the borylated alcohols in good to excellent yields, which can easily be hydrolysed to the eco-friendly corresponding alcohol. The stoichiometric experiments were performed to prove the formation of in-situ generated cerium hydride [Ce]-H as an active catalyst.
Keywords: Cerium; CO2 reduction; Epoxide; Ester; Hydroboration; Lanthanides

Germylene mediated reductive C-C and C-N coupling of an isocyanide and its device application - Gour, Kritika; Pramanik, Debjit; Dash, Soumya Ranjan; Shinde, Dipak Dattatray; Venugopal, Geethu; Vanka, Kumar; Rath, Arup K.; Sen, Sakya S. (Angewandte Chemie-International Edition, 2025)
We have demonstrated a unique reductive coupling of 4-iodophenyl isocyanide, facilitated by a perimidine-based N-heterocyclic germylene (NHGe), which yields a bis-spirogerma compound featuring simultaneous C-C and C-N bond formation. This reaction, which leads to the oxidation of germanium from +2 to +4, represents a significant departure from previously documented isocyanide-germylene interactions. The product exhibits extensive conjugation across its bicyclic C4Ge2N2 framework, conferring distinct photophysical properties, including prominent orange luminescence in both solution and solid states. The photophysical properties are supported by the TD-DFT calculations confirming an n ->pi* transition. The potential application of this compound in optoelectronic devices, particularly as a hole transport layer in PbS quantum dot solar cells, is also explored, with promising preliminary results.
Keywords: Germylene; hole transport layer; Isocyanide; reductive coupling

Magnesium-catalyzed primary, secondary, and tertiary amide hydroboration - Mahata, Biplab; Devaraj, V.; Dash, Soumya Ranjan; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2025)
Catalytic hydroboration of amides is highly important because the resultant amines are commonly found in natural products, pharmaceuticals, agrochemicals, dyes, and other applications. In comparison to the conventional reduction of amides using (over)stoichiometric reductants, hydroboration of amides using magnesium compounds represents a green and sustainable approach because magnesium is both Earth abundant and environmentally benign. However, there is only one report on magnesium-catalyzed deoxygenative hydroboration of secondary and tertiary amides. Here, we describe the synthesis and structural authentication of two new magnesium compounds (1 and 2) featuring a flexible PNP ligand and the utilization of 2 as a catalyst for the pinacolborane-mediated reduction of primary, secondary, and tertiary amides to amines. The reaction scope is explored, and a mechanism is proposed based on experimental and theoretical insights.

Magnesium-ligand cooperation in breaking the O-H and C-H bonds of water and diazoalkane - Sharma, Vishal; Dash, Soumya Ranjan; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2025)
In our previous paper, we reported that the reaction of a tridentate nacnac ligand with a pendant picolyl group, with KHMDS and MgI2, resulted in the formation of a homoleptic hexacoordinate magnesium compound. Here, we show that the analogous reaction of the ligand with CH3MgBr led to a heteroleptic magnesium bromide species (1). Attempts to generate the magnesium hydride species from 1 led to the dearomatization of the pyridine ring, and the resulting product was a magnesium hydroxide (3) presumably generated due to an adventitious amount of water. The reaction of the ligand with nBu2Mg afforded a unique dearomatized magnesium species (2) in high yield. Theoretical calculations reveal the presence of a nonbonding orbital on the magnesium, susceptible to nucleophilic attack. Indeed, the reaction of 2 with H2O/D2O cleaves the O-H/D bond via magnesium-ligand cooperation and generates a magnesium hydroxide (4 and 5). In addition, 2 reacts with Me3SiCHN2 and cleaves the C-H bond to generate another unusual, well-defined magnesium compound with a bridging isocyanide moiety (6) via migration of the SiMe3 group from the carbon to the nitrogen atom. The latter can be described as a dimer of magnesium isocyanamide. DFT calculations were performed to understand the electronic structures of the synthesized molecules.

Pushing the boundaries of pnictogen-bonding organocatalysis: a clash of Sb(III) versus Bi(III) - Sharma, Jyoti; Dash, Soumya Ranjan; Vanka, Kumar (ChemPhysChem, 2025)
The sigma-hole-mediated noncovalent organocatalysis involving the pnictogen (Pn) elements has thus far been explored mostly from nitrogen to antimony, with antimony identified as the most effective catalyst. Herein, density functional theory calculations have been carried out to demonstrate that tri-aryl (Ar)-substituted bismuth(III) complexes can outperform their antimony counterparts in both anion (Cl-) binding and catalytic activity. Using a range of computational methods, a good correlation between the sigma-hole strength, chloride binding affinity, and the reaction barrier is established. Notably, the findings reveal that dispersion interactions are the dominant force in catalysts with weaker sigma-holes, while electrostatic interactions prevail in catalysts with stronger sigma-holes (for the anion abstraction step). In all cases, Bi(III) catalysts emerge as the winner over the Sb(III) analogues. Additionally, beyond the primary Pn. . .Cl interactions, several secondary interactions such as Cl. . .H/F-C(Ar) and Cl-. . . H-C(Si-TBS) also play a significant role in stabilizing the transition states.
Keywords: Antimony; Bismuth; organocatalysis; pnictogen; sigma (sigma) holes

Kekule diradicaloid with a naphthalene spacer - Kundu, Gargi; Pramanik, Debjit; Dash, Soumya Ranjan; Kumar, Ravi; Tothadi, Srinu; Ghosh, Aryya; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2026)
The availability of a diverse array of carbenes led to the generation of a catalog of carbene based Kekule diradicaloids, but the linker in such molecules is mostly limited to phenylene or biphenylene. Here we have prepared a closed-shell Kekule diradicaloid (2) separated by a naphthalene moiety and stabilized by two capping 5-SIDipp [5-SIDipp = 1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] from the reduction of the corresponding dication (1). The combined experimental and computational studies confirm that 2 is in a closed-shell singlet state exhibiting a singlet-triplet energy difference (Delta ES-T) of 18.7 kcal/mol, which is considerably lower than Thiele's version (29.1 kcal/mol).

Switchable solid-state emission in GFP chromophore analogue cocrystals via competing AIE and ACQ pathways - Mali, Bhupendra P.; Dabke, Niteen B.; Sharma, Himanshu; Dash, Soumya Ranjan; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (CrystEngComm, 2026)
We present a crystal-engineering approach enabling switchable solid-state emission (green -> orange -> quenched) in GFP-chromophore analogue cocrystals. The coformer's electronic and supramolecular effect shifts the photophysical pathway: intramolecular CT in cocrystal-I (green) and cocrystal-III (quenched) and intermolecular CT in cocrystal-II, yielding orange emissions and highlighting cocrystallization's power for tunable luminophores.